2017
DOI: 10.1021/acs.langmuir.7b01199
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Microgel-Based Surface Coatings with Linear Thermoresponse

Abstract: We study the swelling and shrinking behavior of core-shell microgels adsorbed on silicon wafers. In these systems, the core is made of cross-linked poly(N-isopropylmethacrylamide) and the shell consists of cross-linked poly(N-n-propylacrylamide). In suspension, these particles exhibit an extended linear swelling behavior in the temperature interval between the lower critical solution temperatures of the two polymers. Using ellipsometry and atomic force microscopy, we show that this linear response is also obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 54 publications
1
67
0
Order By: Relevance
“…This suggests that the particles in suspension exhibit spherical shape, because anisotropic shapes would result in anisotropic projections. Moreover, we have shown that particles at interfaces and in bulk have a similar swelling behavior, 69 suggesting that internal heterogeneities do not affect measurements on surfaces. In AFM, the particles have a mean radius of 42 nm, and a polydispersity of σ = 20.0 %.…”
Section: Resultsmentioning
confidence: 92%
“…This suggests that the particles in suspension exhibit spherical shape, because anisotropic shapes would result in anisotropic projections. Moreover, we have shown that particles at interfaces and in bulk have a similar swelling behavior, 69 suggesting that internal heterogeneities do not affect measurements on surfaces. In AFM, the particles have a mean radius of 42 nm, and a polydispersity of σ = 20.0 %.…”
Section: Resultsmentioning
confidence: 92%
“…Our approach combined several measurements: at first, a pure p(NIPMAM) core ("core-only"), onto which either deuterated or hydrogenated p(NNPAM) shells have been grown. It is stressed that all cores are the same in our studies [57,59,61,89], i.e. the second synthesis step of the shell has been performed with pre-existing cores, enabling thus direct comparisons.…”
Section: Form-free Density Profiles Of Spherically Symmetric Microstrmentioning
confidence: 99%
“…In this work, acrylamide-based, thermoresponsive core-shell microgels with a linear phase transition region are exploited as improved carriers for catalytically active silver nanoparticles. The particles are slightly different compared to those described in [57]. The following general microgel structures were used: p(NIPAM-co-AAc)@p(NNPAM), p(NIPMAMc o -A A c ) @ p ( N N PA M ) , a n d p ( N N PA M -c o -AAc)@p(NNPAM).…”
Section: Applications Of Core-shell Microgels In Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…11 Here, a more complex nanoscale architecture of the microgel particles is investigated: microgel particles based on N-isopropylmethacrylamide (NIP-MAM) (VPTT in water $42 C) 12 are used as seed particles for a second synthesis step, where N-n-propylacrylamide (NNPAM, VPTT of crosslinked homopolymer microgels in water: $22 C) 12,13 is polymerized in the presence of the collapsed seed particles leading to a core-shell structure. 14,15 A peculiar feature of these particles is the linear dependence of the particle size on the temperature. This, especially with the use of the extremely fast responding NNPAM, makes them interesting candidates for sensors or nanoactuators.…”
Section: Introductionmentioning
confidence: 99%